Dietary overlap among white tailed deer and other herbivores at la Mixteca Poblana - Arellano-Alavez, Tania; Mendoza-Martínez, Germán; Villarreal Espino-Barros, Oscar A.; Martínez-García, José Antonio; Hernández-García, Pedro Abel; Plata-Perez, Fernando X. (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of this study was to determine the dietary overlap between white-tailed deer (Odocoileus virginianus) and other herbivores (lagomorphs, cattle, and horses). Vegetation and excreta found in 15 transects 300 m long and 6 m wide were sampled. Using the micro histological technique, a plant reference catalog was elaborated and the fecal samples by species were analyzed to  determine the botanical composition of the diet. It  can be seen that, of 65 plant species collected  presumably consumable by cervids, only 16 were  consumed by them. The microhistological analysis  revealed that the diet of deer and lagomorphs coincides in a single arboreal species, a shrub and a  herbaceous one; However, in the diet of  lagomorphs, the consumption of these three plant  groups represents more than 50% of the diet, while,  in the case of horses and cattle, the diet consisted mainly of a single species of herbaceous or grasses,  respectively. The Pianka index between white-tailed  deer and lagomorphs was 0.26, while compared to cattle and horses it was 0.04 in both cases. As expected from microhistological analysis, the  dietary overlap between deer and other herbivore  species was relatively low. However, the overlap  between white-tailed deer and lagomorphs is 26%  and considering the estimated number of  individuals in the UMA it may be an important element of competition.